Insulin-like growth factor binding protein 5: Diverse roles in cancer - Waters, Jennifer A.; Urbano, Ixchel; Robinson, Mikella; House, Carrie D. (Frontiers in Oncology, 2022)
Insulin-like growth factor binding proteins (IGFBPs) and the associated signaling components in the insulin-like growth factor (IGF) pathway regulate cell differentiation, proliferation, apoptosis, and adhesion. Of the IGFBPs, insulin-like growth factor binding protein 5 (IGFBP5) is the most evolutionarily conserved with a dynamic range of IGF-dependent and -independent functions, and studies on the actions of IGFBP5 in cancer have been somewhat paradoxical. In cancer, the IGFBPs respond to external stimuli to modulate disease progression and therapeutic responsiveness in a context specific manner. This review discusses the different roles of IGF signaling and IGFBP5 in disease with an emphasis on discoveries within the last twenty years, which underscore a need to clarify the IGF-independent actions of IGFBP5, the impact of its subcellular localization, the differential activities of each of the subdomains, and the response to elements of the tumor microenvironment (TME). Additionally, recent advances addressing the role of IGFBP5 in resistance to cancer therapeutics will be discussed. A better understanding of the contexts in which IGFBP5 functions will facilitate the discovery of new mechanisms of cancer progression that may lead to novel therapeutic opportunities